2009
DOI: 10.1002/ptr.2624
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcerogenic activity of the essential oil of Baccharis dracunculifolia on different experimental models in rats

Abstract: Baccharis dracunculifolia DC (Asteraceae), a native plant from Brazil, commonly known as 'Alecrimdo-campo' is widely used in folk medicine to treat inflammation, hepatic disorders and stomach ulcers, and it is the most important botanical source of Southeastern Brazilian propolis, known as green propolis. Its essential oil is composed of non-oxygenated and oxygenated terpenes. In this work, the effects of the essential oil obtained from the aerial parts of B. dracunculifolia on gastric ulcers were evaluated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 26 publications
2
37
0
7
Order By: Relevance
“…Its leaf extracts have been used as an antipyretic, a stomachic, and a health tonic in Brazil (Menezes, 2005). Potent cytotoxic activity against leukemia cells and antiulcer activity have also been reported (Fukuda et al, 2006;Lemos et al, 2007;Massignani et al, 2008). It has been reported that this plant is a source of resin for Brazilian propolis (green propolis), because of the similarity of their chemical constituents (Park et al, 2004).…”
Section: Introductionmentioning
confidence: 91%
“…Its leaf extracts have been used as an antipyretic, a stomachic, and a health tonic in Brazil (Menezes, 2005). Potent cytotoxic activity against leukemia cells and antiulcer activity have also been reported (Fukuda et al, 2006;Lemos et al, 2007;Massignani et al, 2008). It has been reported that this plant is a source of resin for Brazilian propolis (green propolis), because of the similarity of their chemical constituents (Park et al, 2004).…”
Section: Introductionmentioning
confidence: 91%
“…Since ulcerene (50 and 100 mg/kg) significantly (p<0.001) reverted the damage to gastric layer, proposes its ulcer curative property that can be possibly mediated through cytoprotective action on gastric mucosa, as shown by sucralfate (100 mg/kg). Ethanol also contributes to gastric mucosal injury through enhanced intracellular accumulation of calcium that promotes the death of gastric epithelium cells (Massignani et al, 2009). Relaxation of high K + induced pre-contracted isolated rabbit jejunum by a crude extract of ulcerene, suggests the presence of calcium channel blocking activity, strengthen the effectiveness of ulcerene in ethanol induced ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 1 hour prior to induction of ulcer by indomethacin orally given essential oil from Baccharis dracunculifolia at a single dose of 50 mg/kg body weight induced an 80 inhibition of ulcer index while oral cimetidine at a dose of 100 mg/kg body weight only caused 42% inhibition of ulcer index (Massignani et al, 2009). Evening primrose oil, another edible oil, can also dose-dependently prevent the development of gastric ulcer induced by either aspirin or indomethacin (al-Shabanah., 1997).…”
Section: Efficacymentioning
confidence: 99%